Maternal Diet Supplementation with n-6/n-3 Essential Fatty Acids in a 1.2 : 1.0 Ratio Attenuates Metabolic Dysfunction in MSG-Induced Obese Mice. (5th December 2016) - Martin, Josiane Morais; Miranda, Rosiane Aparecida; Barella, Luiz Felipe; Palma-Rigo, Kesia; Alves, Vander Silva; Fabricio, Gabriel Sergio; Pavanello, Audrei; Franco, Claudinéia Conationi da Silva; Ribeiro, Tatiane Aparecida; Visentainer, Jesuí Vergílio; Banafé, Elton Guntendeorfer; Martin, Clayton Antunes; et al.
Abstract : Essential polyunsaturated fatty acids (PUFAs) prevent cardiometabolic diseases. We aimed to study whether a diet supplemented with a mixture of n-6/n-3 PUFAs, during perinatal life, attenuates outcomes of long-term metabolic dysfunction in prediabetic and obese mice. Seventy-day-old virgin female mice were mated. From the conception day, dams were fed a diet supplemented with sunflower oil and flaxseed powder (containing an n-6/n-3 PUFAs ratio of 1.2 : 1.0) throughout pregnancy and lactation, while control dams received a commercial diet. Newborn mice were treated with monosodium L-glutamate (MSG, 4 mg g −1 body weight per day) for the first 5 days of age. A batch of weaned pups was sacrificed to quantify the brain and pancreas total lipids; another batch were fed a commercial diet until 90 days of age, where glucose homeostasis and glucose-induced insulin secretion (GIIS) as well as retroperitoneal fat and Lee index were assessed. MSG-treated mice developed obesity, glucose intolerance, insulin resistance, pancreatic islet dysfunction, and higher fat stores. Maternal flaxseed diet-supplementation decreased n-6/n-3 PUFAs ratio in the brain and pancreas and blocked glucose intolerance, insulin resistance, GIIS impairment, and obesity development. The n-6/n-3 essential PUFAs in a ratio of 1.2 : 1.0 supplemented in maternal diet during pregnancy and lactation prevent metabolic dysfunction in MSG-obesity model.